2018
DOI: 10.1177/0021998318755542
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simultaneous fiber surface treatment and matrix modification on mechanical properties of unidirectional ultra-high molecular weight polyethylene fiber/epoxy/nanoclay nanocomposites

Abstract: Nonpolar structure of ultra-high molecular weight polyethylene fiber leads to a weak interfacial adhesion in ultra-high molecular weight polyethylene fiber reinforced epoxy composite. Herein, synchronized fiber and matrix modifications were utilized so as to improve the interfacial adhesion, resulting in promoting mechanical properties of these composites. For this purpose, the surface of ultra-high molecular weight polyethylene fiber was chemically treated with glycidyl methacrylate and the epoxy resin was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Its smooth surface with a few river‐like markings indicated the brittleness of the pristine epoxy composite, which attests to why the neat Napier/epoxy composite exhibited lower mechanical properties, compared to the other composites containing filler. This was supported by the morphological study by Mohammadalipour et al, which revealed similar images for their neat epoxy composite. The river marking zones were also observed by H. Gao and T. Qiang through SEM analysis of a virgin PLA composite using a larger magnification, confirming that the unfilled composite exhibited a brittle fracture pattern.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Its smooth surface with a few river‐like markings indicated the brittleness of the pristine epoxy composite, which attests to why the neat Napier/epoxy composite exhibited lower mechanical properties, compared to the other composites containing filler. This was supported by the morphological study by Mohammadalipour et al, which revealed similar images for their neat epoxy composite. The river marking zones were also observed by H. Gao and T. Qiang through SEM analysis of a virgin PLA composite using a larger magnification, confirming that the unfilled composite exhibited a brittle fracture pattern.…”
Section: Resultssupporting
confidence: 76%
“…This suggested that, at the 5 wt% nanoclay content, the composites absorbed more work of fracture and consequently showed higher mechanical resistance. Several studies have proved that, with the addition of nanofiller to a composite, the crack propagation induced by any test was forced to follow a tortuous path . As a result, the nanocomposites showed better resistance to the applied force, describing tougher behavior, compared to the pristine one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Major constituents of fibre reinforced polymer (FRP) composites are matrix and reinforcement. Thermosetting or thermoplastic resins used as matrix material [5], and synthetic or natural fibre/fabric is used as reinforcements [9][10][11]. Epoxy is the most widely used thermoset matrix and most of the industries use epoxy for fabrication of composites due to their qualities like low processing temperature, thermal stability, adhesion, and hold good mechanical properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy is the most widely used thermoset matrix and most of the industries use epoxy for fabrication of composites due to their qualities like low processing temperature, thermal stability, adhesion, and hold good mechanical properties [4]. After conventional synthetic fibres like Glass fibre, Kevlar fibre, and Carbon fibre; UHMWPE fibres are most widely used as reinforcement in the recent days [5][6][7][8] because-of distinguished physical and mechanical properties UHMWPE fibres considered as third generation synthetic fibres [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%